Efficacy and safety of PCSK9-Inhibitors in the real-world: data from a clinical registry. (25th November 2020) - Saba, P.S; Murgia, A; Gazale, E; Terrosu, P; Sanna, G.D; Parodi, G
Abstract: Background: To date, little information is available on the real impact of PCSK9 inhibitors in terms of reducing cholesterolemia, events and the actual tolerability in the so-called "real world". This lack of information is substantially related to the fact that these drugs have only been marketed recently. In Italy, few centres are licensed to prescribe these drugs. This, on the one hand, limited the number of patients to whom the new therapy was offered but, on the other hand, "concentrated" the observations in a few centres, making it possible to more easily collect the few data currently available. The Cardiology Unit of our university hospital is the only prescribing centre in the North Sardinia and therefore represents the natural collector of all the prescriptions of this drug in this wide geographical area. Purpose: The aim of the study was to evaluate the efficacy and tolerability of PCSK9 inhibitors in the current clinical practice. Methods: Data were collected reviewing all Alirocumab and Evolocumab prescriptions provided by the Cardiology Unit of our university hospital included in the Italian National Drug Agency (AIFA) registry from February 2017 to October 2019. In order to collect complete clinical information, all patients were interviewed regarding their health status, the on-treatment cholesterol levels and the possible appearance of side effects or cardiovascular events. Results: In the reference period, 111 patients (58.9% males, age 63±10 years) received PCSK9-Inhibitors prescription (52.7% Evolocumab, 47.3% Alirocumab), 86.5% as secondary prevention. Statin intolerance was the indication for PCSK9-Inhibitors in the majority (73.3%) of patients. LDL cholesterol at eligibility evaluation was 175±50 mg/dl and reduced to 87±44 mg/dl (p<0.0001) at last follow-up assessment (median 12.3 IQR 6.8–21.4 years). Maximal per cent variation of LDL-cholesterol was achieved already after 6 months of therapy (−45±3% vs basal). No attenuation in LDL-cholesterol lowering was observed; conversely, LDL levels continued to reduce during treatment (p for linear trend = 0.01; Figure 1). During follow-up, 8 patients (7.2%) stopped PCSK9 inhibitors: 2 subjects (1.8%) for side effects certainly related to the drug (flu-like syndrome, allergic reaction), 4 for possible side effects (myalgia, abdominal pain), the remaining for other reasons. Conclusions: Clinical use of PCSK9 inhibitors confirms its efficacy and safety also in the "real world" setting. LDL reduction occurs early during the treatment and shows a significant trend in further reduction during the observation period. More than 90% of subjects tolerate and persist in PCSK9 inhibitors treatment in the long-term follow-up. Funding Acknowledgement: Type of funding source: None